A Critical Analysis of Regional Program Evaluation Practice in Kazakhstan - N. N. Battalov (Экономика: стратегия и практика)
In recent years the development of public program evaluation has received growing attention in Kazakhstan. An institutional and legal base for program evaluation has been established. However, the examination of literature has evidenced that there have been rudimentary attempts to interrogate evaluation practice, particularly at the regional level. It is still not well known how effective or valuable it is. It is imperative to run a diagnostic and assess the evaluation system to answer this question. This article aims to evaluate the quality of regional program evaluation practice in Kazakhstan. It applies a meta-evaluation tool to understand the extent to which such practice complies with three fundamental and recognized evaluation standards: namely, value, validity, and utility. As a sample, the study used evaluation reports conducted by regional Audit commissions. This research is the first attempt to apply established evaluation standards to the Kazakhstani context. Therefore, it was assumed that some discrepancies with the standards may occur. Having confirmed this hypothesis, the findings indicate that regional program evaluation falls far short of these standards. The paper identified many conceptual and methodological problems, which seriously compromise the validity and soundness of evaluation practice. It is expected that it will stimulate discussion in academic and subject matter expert circles. Furthermore, having identified key areas for improvement, the study may help reform the evaluation field and contribute to better policy- and decisionmaking, thus saving taxpayers’ money and improving people’s wellbeing. In the end, the research put forward several recommendations for strengthening evaluation practice.